Determinants of Teenage Pregnancy in Tanzania - Ayoub, Harun Yussuf; Siregar, Kemal Nazaruddin (UI Scholars Hub, 2025)
Teenage pregnancies are among the leading public health problems in Tanzania. This was linked to limited education, socioeconomic disparities, cultural barriers, and inadequate access to healthcare centers. Thus, this study aims to explore the prevalence and predictors of teenage pregnancy among adolescent women using data from the 2022-2023 Tanzanian Demographic Health Survey (TDHS). The research design employed a cross-sectional approach and utilized TDHS data. The population for this study was female adolescents, while the sample was 7,545 adolescent women aged 15-24 years. Predictor variables were education level, socioeconomic status, place of residence, employment status, and lifestyle factors, including alcohol consumption and smoking status. Logistic regression analyses were performed. The results of this study found that alcohol consumption was the highest risk factor that contributed to teen pregnancy, as teenage drinkers were found to have significantly higher odds of becoming pregnant (aOR=2.21). Also, economic status was found to further elevate the risk of teen pregnancy in that adolescents from families of lower socioeconomic status were more susceptible to the harmful effects of alcohol consumption (aOR=1.64). Rural residence was also significantly associated with odds for adolescent pregnancy, indicating the need for strengthened interventions among rural youth. The significance of pluralistic policies to reduce alcohol consumption, improve education and reproductive health care, and resolve the socio-economic problems among adolescents, particularly in disadvantaged and rural areas.